WOMEN'S ACTIVITIES IN THE LIFE OF MUHAMMAD (570-632 AD) - Shidqy Munjin (UIN Sunan Gunung Djati Bandung, 2019)
The main problem in this study is to uncover three problems related to women in the time of Muhammad. First, regarding the position of women during the time of Muhammad. Second, concerning the extent of women's involvement in various activities during the time of Muhammad, both in the period before and after it. Third, what problems were faced by women at that time and how they affected their activities. This research is based on the library research of the earliest classic books in the UIN SGD Bandung Library and the al-Musaddadiyyah Garut Foundation Library, such as Ibn Ishaq, Ibn Hisham, al-Waqidi, Ibn Sa'd, and al- Tabari. The results of this study indicate that Muhammad was a person who cared deeply about human rights especially those relating to women. This conclusion is proven by his attitude which always defends the oppressed. He always displayed this defence attitude before being appointed as a prophet, and even more firmly when he was appointed as a prophet. The different characteristics of Muhammad's attitude towards women before and after the prophecy were influenced by economic factors, security, and the social system that prevailed in each of these periods.